School Principal’s Leadership Style and Its Impact on School Management - Mursiani, Mursiani; Widayatsih, Tri; Fahmi, Muhammad (Journal of Social Work and Science Education, 2023)
This study aims to (1) identify and describe the leadership style adopted by the Principal of SMP 5 Tulung Selapan, (2) determine the impact of this leadership style on school management and (3) strategies for improving teacher performance. The method used in this research is qualitative research using in-depth interviews which have been conducted directly with the informants. The validity of the data was carried out with the persistence of observers and the triangulation method. The conclusions obtained in this research are, (1) The principal’s leadership in an effort to improve teacher performance at SMP Negeri 5 Tulung Selapan, Tulung Selapan sub-district, Ogan Komering Ilir Regency has been carried out quite well even though it has not been supported by complete facilities (2) Teacher performance in carrying out learning is good enough, and (3) the principal’s efforts to improve teacher performance in carrying out learning are carried out, among others, through several activities, namely: a) carrying out teacher performance assessments, b) carrying out academic supervision of learning carried out by teachers in class, c) carrying out follow-up results supervision.